(untitled) (Tanzania Journal for Population studies and Development, 2024)
Globally, water concerns stemming from human factors are evident, and the Kagera River Basin exemplifies this challenge. This study investigated the influence of human elements on transboundary water resource management in the Kagera River Basin. Utilizing focus group discussions, household surveys, key informant interviews, and field observations, the study analysed land use changes via remote sensing; and processed quantitative data using SPSS 20 and ArcGIS 10.4. Results highlighted economic, political, and social factors as key factors influencing transboundary water resource management. The institutional analysis identified major players to include the Ministry of Water, Lake Victoria Basin Water Board, NELSAP, Ministry of Agriculture, village governments, and CONCERN/OXFAM. Non-climatic factors such as water infrastructure management, socio-economic factors, conflicting water uses, agricultural practices causing soil erosion, and land use/cover changes were identified as central to transboundary water resource challenges. Agricultural expansion and land use shifts in the basin in 1986, 2000 and 2021 were pinpointed as contributors to water resource challenges, impacting availability, access, and quality. Anthropogenic-driven land use changes emerged as significant contributors to pollution, habitat loss, and alterations in water quality. While human factors substantially influence water resources, their impact is exacerbated by anthropogenic activities. Thus, fostering collaborative planning and stewardship initiatives at the local level is crucial for sustaining transboundary water resources. This involves engaging community members and leaders in developing resilience plans and initiating international cooperation, and innovative participatory approaches for effective transboundary water resources management.